Cross-Sectional Risk Factors of Anterior Knee Pain in Adolescents - Borschneck, Gregory; St. John, Laura; Brundage, Kristy; Borschneck, Daniel Patrick (Frontiers in Pain Research, 2021)
Background: Anterior knee pain is a common complaint amongst adolescents, which can both be persistent, and in some cases, disabling. This study investigated a series of potential risk factors potentially linked to the onset of anterior knee pain. Methods: Questionnaires were distributed amongst 367 10–15 years-olds enrolled in the local school board. These surveys included questions on sex, age, sport participation, and history of anterior knee pain verified by a physician. Bivariate correlations and a binomial logistic regression were conducted. Overall rate of AKP in the population studied was 7.4%. The results indicated that past history of knee pain, age, and increased sports participation significantly correlated with increased risk of AKP. AKP was significantly more common in females than males. While sex, height, age, overall sport participation, participation in specific sports, and history of knee injury all contributed to the binomial model.